Intraoperative radiotherapy for early breast cancer — insufficient evidence to change practice - Sasieni, Peter D. (Nat Rev Clin Oncol, 2020)
We argue that the evidence remains insufficient for use of intraoperative radiotherapy (IORT) in women with early stage breast cancer outside of a clinical trial, as the recently reported TARGIT-A trial does not provide sufficient evidence to conclude that IORT is superior to no radiotherapy.